The occurrence and curing of stuttering during the use of methylphenidate for ADHD in childhood : An inconsistent relationship - Fahri Çelebi; Tayfun Kara (Acta Medica Alanya)
Stuttering is a childhood onset fluency disorder in speech. It has been suggested to be associated with brain anatomy, functionality or the dysregulation of the dopaminergic activity. Attention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders in childhood and adolescence. Psychostimulant medications are widely used for the psychopharmacologic treatment of ADHD. In this article, two boys who have ADHD with opposite reactions after methylphenidate (MPH) treatment in terms of fluency in the speech are presented. In the first case stuttering was induced with MPH while in the second case stuttering was resolved after MPH treatment. Although MPH seems to have opposite effects on stuttering in our cases, our case report points that dopaminergic system may play a role for the onset of childhood onset fluency disorder. More comprehensive studies are needed to show the neurodevelopmental process and the mechanisms related with ADHD, stuttering and MPH treatment.